CONVENTION REPORT. (The Accounting Review, 1939)
The article presents information on the proceedings of the 23rd annual convention of the American Accounting Association, held at Detroit Leland Hotel, Detroit, Michigan, between December 28 and 30, 1938. The chairman introduced the representative of the American Institute of Accountants, Thomas H. Evans. The first order of the regular business was the reports of officers. The president addressed that a considerably larger Life Membership Fund would enable them to publish a number of worthwhile studies which would add to the prestige of the association. He adds that the cooperation of all members and especially of the heads of accounting departments and others in keeping the directors informed of projects which are in the offing and in putting the committee in touch with promising men who might undertake studies on subjects needing research works. He admits that their educational committee has not been assigned any particular projects this year, but several studies of collegiate training in business and accounting are being made by other organizations, and it is likely that they shall be called upon in the near future to take part in one or more of these.